2017
DOI: 10.1111/ajr.12380
|View full text |Cite
|
Sign up to set email alerts
|

Time to delivery: Transfers for threatened preterm labour and prelabour rupture of membranes in Western Australia

Abstract: Objective: To describe the outcomes of patients transferred to King Edward Memorial Hospital (KEMH) with signs of labour at preterm gestations. Design: A retrospective observational study of the 69 cases transferred to KEMH during 2015. Setting: Patient transfers from all locations across Western Australia (WA) to the sole tertiary perinatal centre in Perth. Participants: Pregnant women within WA with threatened or actual preterm labour (PTL) or preterm prelabour rupture of membranes (PPROM) between 23 and 32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…23 Access to care may also be a factor, such as when care is sought or if the mother had to be transferred, although in our analysis the relationship persisted despite adjusting for both number of prenatal care visits and maternal transfer. 25,26 Underlying all of these factors is the concern that systemic racism and discrimination may be contributing to these disparities. 11,27 The administration of ACS to women who deliver prematurely improves neonatal outcomes including death, respiratory distress syndrome, intraventricular hemorrhage, necrotizing enterocolitis, need for mechanical ventilation, and systemic infection within the first 48 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Access to care may also be a factor, such as when care is sought or if the mother had to be transferred, although in our analysis the relationship persisted despite adjusting for both number of prenatal care visits and maternal transfer. 25,26 Underlying all of these factors is the concern that systemic racism and discrimination may be contributing to these disparities. 11,27 The administration of ACS to women who deliver prematurely improves neonatal outcomes including death, respiratory distress syndrome, intraventricular hemorrhage, necrotizing enterocolitis, need for mechanical ventilation, and systemic infection within the first 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…23 Access to care may also be a factor, such as when care is sought or if the mother had to be transferred, although in our analysis the relationship persisted despite adjusting for both number of prenatal care visits and maternal transfer. 25 26 Underlying all of these factors is the concern that systemic racism and discrimination may be contributing to these disparities. 11 27…”
Section: Discussionmentioning
confidence: 99%
“…Pre-hospital and retrieval medicine experts recommend that a patient with cervical dilatation greater than 5cm, should not be transferred due to the risk of precipitous birth in-flight(14). One study of rural women transferred to a tertiary hospital for signs of preterm labour showed that cervical dilatation (in conjunction with nulliparity and regular contractions) was associated with shorter time-to-birth(29). In nearly half of all cases in this cohort, no cervical examination was performed, possibly due to lack of confidence in performing the exam, or because the examination would not change the need for retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…12 Careful consideration is required to determine which women can be safely transferred using midwifery and obstetric expertise, as well as better predictors of preterm delivery. 34 35 The majority of women in threatened preterm labour do not deliver within 24 hours of presentation [36][37][38] and infants rarely deliver during transportation. 34 36 39 This suggests the window of opportunity for IUT may be greater than currently perceived and improving care pathways could help reverse the declining IUT rate.…”
Section: Discussionmentioning
confidence: 99%